2019
DOI: 10.1177/1321103x18821198
|View full text |Cite
|
Sign up to set email alerts
|

Musical communication in scaffolding young learners’ expressive agency

Abstract: In a qualitative study of the nature of musical communication during scaffolding music learning, the most important themes to emerge reflected the role of musical communication in blossoming young learners’ expressive agency. The study focused on two different groups of young piano learners (aged 4–9) during collaborative (listening, creating, and performing) problem-solving experiences. Working as a teacher-researcher in the context of my own studio piano classes, I documented verbal and nonverbal interaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…First, it appears that creative activities that are monitored by a professional artist can contribute to the development of intrapersonal skills among 4-to 5-year-olds, such as autonomy, and initiative-taking (Aubrey & Dahl, 2013). 1 Kondo (2020) for instance, reported the benefit of a 13-week piano lessons program on young children's autonomy, and feeling of self-efficacy. Likewise, other domains of creativity, such as visual arts, music, dance, seem to provide both a sense of enjoyment and autonomy among 2 year-old children (Fernandez-Santin & Feliu-Torruella, 2020).…”
Section: Do Creative Activities Contribute To the Resilience Of Young...mentioning
confidence: 99%
See 1 more Smart Citation
“…First, it appears that creative activities that are monitored by a professional artist can contribute to the development of intrapersonal skills among 4-to 5-year-olds, such as autonomy, and initiative-taking (Aubrey & Dahl, 2013). 1 Kondo (2020) for instance, reported the benefit of a 13-week piano lessons program on young children's autonomy, and feeling of self-efficacy. Likewise, other domains of creativity, such as visual arts, music, dance, seem to provide both a sense of enjoyment and autonomy among 2 year-old children (Fernandez-Santin & Feliu-Torruella, 2020).…”
Section: Do Creative Activities Contribute To the Resilience Of Young...mentioning
confidence: 99%
“…Furthermore, research has highlighted how creative activities can aid individuals in managing and regulating challenging emotions (Brown, 2007; Loizou & Loizou, 2019). Likewise, the impacts of art‐based programs on the autonomy, self‐efficacy, and positive emotions of 4‐ and 5‐year‐old children have been identified—these factors stand as promotive elements of resilience and are integral outcomes of resilience itself (Aubrey & Dahl, 2013; Deci et al., 2001; Fernandez‐Santin & Feliu‐Torruella, 2020; Kondo, 2020; Masten & Barnes, 2018; Montgomery, Miller, Foss, Tallakson, & Howard, 2017). Yet, despite these insights, the existing literature has lacked a comprehensive synthesis that substantiates our understanding of whether, and potentially which, creative activities contribute to the factors that enhance the resilience of young children.…”
Section: The Positive Effects Of Creative Activities On Adult's Resil...mentioning
confidence: 99%
“…According to Desyandri (2017), values are internalized in the form of self-expression through singing. Moreover, it has been concluded that when children are engaged in 'musical scaffolding,' their capacity to express is also supported (Kondo, 2019).…”
Section: Pretest and Post Test Scores Of Social And Emotional Developmentioning
confidence: 99%
“…Some small-scale studies have used lesson observation to investigate how tutors worked with their pupils 1 on expressive performance. Kondo (2019) observed some of her own piano pupils (5-6-year-olds) during their small group lessons in a year-long study. Based on her observations, she proposed that 'improvisational musical communication can engender and develop children's inherent communicative potential and expressive power' (Kondo, 2019, p. 12).…”
Section: Introductionmentioning
confidence: 99%